PENGARUH PENGGUNAAN TEPUNG JAHE (Zingiber offinale) DALAM RANSUM TERHADAP SALURAN PENCERNAAN DAN HATI PADA AYAM KAMPUNG UMUR 12 MINGGU - Cahyono, Endra Dwi; Atmomarsono, Umiyati; Suprijatna, Edjeng (Animal Agriculture Journal, 2012)
This study aims to determine the effect of ginger on gastrointestinal tract which includes the weight of the digestive tract, the length of the small intestine, liver weight and liver color. Materials used in this research were 240 birds of Day Old Chicken (DOC). Feed that is given are corn, rice gran, soybean meal, coconut cake, PMM, fish meal, top mix TM and ginger powder in 17% protein and 2900 kcal/kg metabolizable energy. Statistic used in this research were Completely Randomized Design (CRD) Split Plot pattern with 4 treatments and 5 replications of diets (ad libitum provided), but on the ginger treatments feed gave once in three days, T0 = diets without using ginger powder, T1= 1% usage of ginger powder, T2= 2% usage of ginger powder, T3= 3% usage of ginger powder. The result show that native chicken relative weight of digestive tractus age of 12 weeks (T0= 13,16%, T1= 13,38%, T2= 12,51%, T3= 12,94), Length of small intestine (T0= 129,1 cm, T1= 123,9 cm, T2= 123,7 cm T3= 121,4 cm), relative weight of liver (T0= 2,42%, T1=2,33%, T2=2,53%, T3= 2,37%). The liver color of male native chicken with T0 treatment showed dark color (score 4), male native chicken with T0 treatment showed normal color (score 3) (descriptive). Gender of male didn’t make a significant effect on liver color. Gender of female makes a significant effect on liver color (based on H test from Kruskal Wallis). The conclusion showed that there’s no significant effect of using ginger powder (P>0,05) on weight of digestive, length of intestine, and weight of liver. There is negative effect of using 3% of ginger powder on liver color.Key words: native chicken, ginger powder, digestive tractus, liver.